2015
DOI: 10.3174/ajnr.a4579
|View full text |Cite
|
Sign up to set email alerts
|

Using Body Mass Index to Predict Needle Length in Fluoroscopy-Guided Lumbar Punctures

Abstract: BACKGROUND AND PURPOSE:Predicting the appropriate needle length to use in oblique interlaminar-approach fluoroscopyguided lumbar punctures in patients with a large body mass index is difficult. Using the wrong needle length can lead to an increased radiation dose and patient discomfort. We hypothesized that body mass index could help determine the appropriate needle length to use in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(28 reference statements)
0
8
1
Order By: Relevance
“…The formulae (Fig 3) derived from our study differ from that which has been reported previously by a different group 8 . A potential explanation for this is the difference in average BMI per study.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The formulae (Fig 3) derived from our study differ from that which has been reported previously by a different group 8 . A potential explanation for this is the difference in average BMI per study.…”
Section: Discussioncontrasting
confidence: 89%
“…The formulae (Fig 3) derived from our study differ from that which has been reported previously by a different group. 8 A potential explanation for this is the difference in average BMI per study. Our cohort contained a greater proportion of patients with BMIs classified as normal or overweight (39.6% and 30.1% vs. 22% and 22%, respectively) and a smaller proportion of patients with BMIs classified as obese (25.7% vs. 52%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthropometric data included age, gender, height, weight, calf dominance and BMI [22]. Further, calf length (measured from the popliteal fossa to the calcaneal tuberosity) and calf girth (assessed in the mid-third and distal-third distance of the calf length) were also calculated (Figure 1).…”
Section: Participantsmentioning
confidence: 99%